Dynamic simulation of hazard analysis of radiations from LNG pool fire - Sun, Biao; Guo, K.; Pareek, V. (Elsevier Ltd, 2015)
Because of its highly flammable nature, any accidental release of liquefied natural gas (LNG) could possibly pose significant fire hazard. In this study, a computational fluid dynamics (CFD) model was used to analyze this hazard around an existing LNG station. By assuming an LNG pool fire occurring in an impoundment area, dynamic simulations of flame development have been carried out. In order to provide more reliable simulation results, a study was first conducted to determine the mesh independence and suitable time step. The results of CFD simulations were also compared with those using the commonly-used phenomenological model. The simulation results showed that LNG tanks in the neighbor dike area could withstand the received radiant heat flux, and the areas involving human activities, such as security office and public area, were also secure enough for people to escape from the hazards. LNG vaporizers, which are often located close to tank area, could possibly receive relatively higher radiant heat flux. High temperature achieved on vaporizers could cause material failure. CFD calculations have also indicated that increasing the spacing distance or using flowing water curtain could reduce this temperature. It is concluded that CFD method is significantly more effective to account for LNG hazard analysis and provide realistic results for complicated scenarios, thus providing meaningful information for safety consideration.